Silaindacenodithiophene‐Based Fused‐Ring Non‐Fullerene Electron Acceptor for Efficient Polymer Solar Cells1. Issue 6 (17th April 2018) - Nian, Yaowen; Wang, Zhen; Jiang, Haiying; Feng, Shizhen; Li, Suhan; Zhang, Lianjie; Cao, Yong; Chen, Junwu
Abstract: In this work, a new A‐D‐A type nonfullerene small molecular acceptor SiIDT‐IC, with a fused‐ring silaindacenodithiophene (SiIDT) as D unit and 2‐(3‐oxo‐2, 3‐dihydroinden‐1‐ylidene)malononitrile (INCN) as the end A unit, was design and synthesized. The SiIDT‐IC film shows absorption peak and edge at 695 and 733 nm, respectively. The HOMO and LUMO of SiIDT‐IC are of −5.47 and −3.78 eV, respectively. Compared with carbon‐bridging, the Si‐bridging can result in an upper‐lying LUMO level of an acceptor, which is benefit to achieve a higher open‐circuit voltage in polymer solar cells (PSCs). Complementary absorption and suitable energy level alignment between SiIDT‐IC and wide bandgap polymer donor PBDB‐T were found. For the PBDB‐T:SiIDT‐IC based inverted PSCs, a D/A ratio of 1: 1 was optimal to achieve a power conversion efficiency (PCE) of 7.27%. With thermal annealing (TA) of the blend film, a higher PCE of 8.16% could be realized due to increasing of both short‐circuit current density and fill factor. After the TA treatment, hole and electron mobilities were elevated to 3.42 × 10 −4 and 1.02 × 10 −4 cm 2 ·V −1 ·s −1, respectively. The results suggest that the SiIDT, a Si‐bridged fused ring, is a valuable D unit to construct efficient nonfullerene acceptors for PSCs. Abstract : Silaindacenodithiophene (SiIDT), a Si‐bridged fused ring, is introduced to construct a new narrow band gap non‐fullerene acceptor. Its polymer solar cells combining a well‐known PBDB‐T donor can show a power conversion efficiency up to 8.16%.